Pro-WEAI for market inclusion - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
Many development agencies are designing and implementing value chain interventions that aim to reach, benefit, and empower rural women. Monitoring and evaluating the success of these value chain interventions requires tools to identify the constraints women and men face and to track empowerment across multiple nodes of the value chain. The project-level Women’s Empowerment in Agriculture Index for market inclusion (pro-WEAI+MI) includes the core pro-WEAI module plus new complementary indicators to investigate barriers to market access and inclusion for different value chain actors. The survey also offers several optional indicators, including access to reliable sanitation and sexual hostility in the working environment, to assess the empowerment environment. These additions and enhancements increase pro-WEAI’s ability to measure and contextualize empowerment and inclusion across value chains.